2010
DOI: 10.1167/iovs.09-4496
|View full text |Cite
|
Sign up to set email alerts
|

Effects on Choroidal Neovascularization after Anti-VEGF Upload Using Intravitreal Ranibizumab, as Determined by Spectral Domain-Optical Coherence Tomography

Abstract: With SD-OCT, CNV size can be two-dimensionally determined and followed up after intravitreal anti-VEGF treatment. In only 4% of CNV was enlargement observed, whereas in 78%, CNV architecture appeared qualitatively unchanged, independent of retinal edema. Quantitative measurements underlined stable CNV diameters for all subtypes but revealed significant reduction of thickness especially for classic CNV components. In this series, ranibizumab monotherapy was able to morphologically stop further CNV growth but, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 15 publications
3
31
0
3
Order By: Relevance
“…Blue-light fundus photography and autofluorescence images eliminate the possibility that HRD could be the focal accumulation of pigment or lipofuscin granules. These imaging techniques do not reveal any alteration supporting this origin, and this has also been agreed by other investigators [2,3,4,5,6,7,8,9,10,11,12,13]. Punctuate hemorrhages are usually larger in size and are located mainly in the inner retinal layers.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Blue-light fundus photography and autofluorescence images eliminate the possibility that HRD could be the focal accumulation of pigment or lipofuscin granules. These imaging techniques do not reveal any alteration supporting this origin, and this has also been agreed by other investigators [2,3,4,5,6,7,8,9,10,11,12,13]. Punctuate hemorrhages are usually larger in size and are located mainly in the inner retinal layers.…”
Section: Discussionsupporting
confidence: 87%
“…These advances may provide not only a better understanding of pathogenesis and evaluation of treatment efficacy for neovascular AMD, but could also add new findings on OCT (besides central macular thickness) that may be important to guide management strategies in patients affected by macular disease [7,8,9,10]. …”
Section: Introductionmentioning
confidence: 99%
“…Visual acuity was improved with the restoration of disrupted IS/OS line. The results of this study are consistent with those of previous studies in exudative ARMD, suggesting that the integrity of the photoreceptor layer is associated with visual outcome after photodynamic therapy or anti-VEGF therapy [7][8][9][10].…”
Section: Resultssupporting
confidence: 90%
“…Framme et al [9] observed CNV structural changes before and after anti-VEGF therapy in 78 eyes with neovascular AMD. They reported significant reduction in CNV thickness and showed no significant difference in CNV diameter.…”
Section: Resultsmentioning
confidence: 99%
“…Optical coherence tomography visualizes the arrangement of different layers and distribution of pathologic fluid or tissue within or below the retina. Recently, using OCT, several authors have suggested that classic CNV tends to be subretinal, 6,10,[13][14][15][16] while occult CNV appears as a PED. 6,10,[17][18][19][20] Both time-domain OCT and SD-OCT have demonstrated a good correlation between the size of the highly reflective subretinal lesions on OCT and the size of the classic CNV on FA.…”
Section: Discussionmentioning
confidence: 99%